The tactical berth allocation problem with time-variant specific quay crane assignments. (May 2021) - Thanos, Emmanouil; Toffolo, Tulio; Santos, Haroldo Gambini; Vancroonenburg, Wim; Vanden Berghe, Greet
Highlights: The continuous berth allocation problem with time-variant, specific quay crane assignments is studied at a tactical level. A MIP model is introduced and instances with 10 vessels, 20 cranes and 100 berth positions are solved to optimality. A Remove & Reinsert heuristic is developed which can accommodate both fixed and flexible departure time settings. Allowing flexible departure times enables to reduce container transshipment distances by up to 26%. Abstract: Decision support systems and automated planning have become essential for the effective management of seaport container terminals. Due to ever-increasing levels of maritime traffic and freight transportation, terminals are expected to facilitate their intra-yard operations while respecting tighter vessel schedules. Employed models must therefore be capable of providing berth allocation decisions which are not only efficient, but also physically realizable. The present paper addresses the continuous Berth Allocation problem with Specific Quay Crane Assignments, with the aim being to minimize container transshipment distances within the terminal yard. An integrated mathematical formulation is presented which considers various real-world properties such as limited crane ranges and quay discontinuity. Based on this formulation, we also introduce a fast local search-based heuristic, capable of accommodating both fixed and flexible departure time settings. The proposed heuristic is evaluated upon a set of instances which cover a wide range of diverse layout specifications and the solutions are compared against those obtained by a state-of-the-art commercial solver. Experimental results confirm the effectiveness of the heuristic and demonstrate how significantly improved schedules can be obtained when flexible departures are permitted.